(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Society of the 21st century is marked by a high-speed development of processes of change, innovation and globalization. From the beginning of this century, the process of globalization, which has shown the interconnection and integration between certain states, technologies, economic systems and cultures, continues to show its effectiveness in a wide way. These changes are not only affecting economic and political ties between countries, but also radically changing human demands for everyday life, behavior and knowledge. In the 21st century, globalization has deepened not only at the geographical, but also at the economic and cultural level. One of the main factors in this process is the development of Information Technology.